Perancangan Model Strategis Pengembangan Desa Wisata Sangeh: Optimalisasi Potensi Lokal untuk Mewujudkan Pariwisata Berkelanjutan yang Berdaya Saing - Surya Wijaya, Nyoman; Darsana, I Made (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2026)
The development of Sangeh Tourism Village faces strategic challenges arising from unequal tourism development across Badung Regency and the increasing phenomenon of overtourism in South Badung. Although endowed with strong natural and cultural potential, Sangeh has not yet been optimally managed, particularly in terms of governance, promotion, and the integration of cultural values into its tourism products. This study aims to formulate development strategies to establish Sangeh as a sustainable cultural tourism village and to design a management model that integrates economic, social, cultural, and environmental dimensions. The research employs a qualitative-descriptive approach through field observations, in-depth interviews, and a review of relevant regulations on tourism village development. The findings reveal that institutional strengthening, cultural-based product innovation, digital promotion, and multi-stakeholder collaboration are key strategies to enhance the village's competitiveness. Additionally, the proposed sustainable tourism village development model emphasizes a balanced approach to community empowerment, cultural preservation, environmental protection, and local economic growth. These results are expected to serve as a reference for government bodies, tourism village managers, and stakeholders in designing sustainable development policies and programs for Sangeh Tourism Village.